2010
DOI: 10.1007/s00436-010-1800-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Giardia activity of phenolic-rich essential oils: effects of Thymbra capitata, Origanum virens, Thymus zygis subsp. sylvestris, and Lippia graveolens on trophozoites growth, viability, adherence, and ultrastructure

Abstract: The present work evaluates the anti-Giardia activity of phenolic-rich essential oils obtained from Thymbra capitata, Origanum virens, Thymus zygis subsp. sylvestris chemotype thymol, and Lippia graveolens aromatic plants. The effects were evaluated on parasite growth, cell viability adherence, and morphology. The tested essential oils inhibited the growth of Giardia lamblia. T. capitata essential oil is the most active followed by O. virens, T. zygis subsp. sylvestris, and L. graveolens oils. The tested essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 43 publications
4
46
0
3
Order By: Relevance
“…Essential oils and essential oil constituents have been studied, in the last years, for their activity on several pathogenic protozoan as Giardia sp. [10][11][12], Leishmania sp. [13,14], and Trypanosoma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Essential oils and essential oil constituents have been studied, in the last years, for their activity on several pathogenic protozoan as Giardia sp. [10][11][12], Leishmania sp. [13,14], and Trypanosoma sp.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have indicated that extract of folklore plants with phenolic consistent shows great anti giardial effects (29,30). Some constituents have been isolated from S. lavandulifolia, mainly flavonoids with high antibacterial, antifungal, and anti parasital characteristics (10,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…The oregano plant has been studied and tested as an anticancer, pesticide and antimicrobial food preservative Machado et al, 2010;Martínez-Rocha, Puga, Hernández-Sandoval, Loarca-Piña, & Mendoza, 2008;Zheng & Wang, 2001). The chemical composition of the stem has been studied due to its important content of flavonoids, which can contribute to the development of new compounds for agronomy and medicine applications (González-Güereca, Soto, Kite, & Martínez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…El orégano se ha estudiado y probado como conservador de alimentos, anticancerígeno, plaguicida y antimicrobiano (Machado et al, 2010;Martínez-Rocha, Puga, Hernández-Sandoval, LoarcaPiña, & Mendoza, 2008;Zheng & Wang, 2001). También se ha estudiado la composición química del tallo por su contenido importante de flavonoides que pueden contribuir al desarrollo de nuevos compuestos con aplicaciones en la agronomía y medicina (González-Güereca, Soto, Kite, & Martínez, 2007), lo cual le da aún más importancia a la planta.…”
Section: Introductionunclassified